Management of Resistance Media in Wartime - Thuraya, Mohammed Saeed (Journal of Humanities & Social Sciences, 2021)
The study aimed to hinder the ability of the Resistant Media Department in the Palestinian Al-Aqsa satellite channel during the time of war, which was between December 28, 2008 and January 17, 2009, and the study relied on the descriptive and analytical method using the questionnaire and the interview. Arab and foreign satellite channels and agencies who worked during the war, and their number was 77. The five-point Likert scale was used in the construction of the questionnaire, and the stability of the questionnaire was verified through the (Alpha Cronbach) coefficient, the choice of (T-test) and the (One way Anova) test. The study showed that the Resistance Media Department in the satellite channel succeeded in achieving steadfastness and steadfastness among the people of the Gaza Strip, with an average of 3.8 and the percentage was 76.8%. The Resistant Media Department in the satellite channel succeeded in achieving victory and support in the western street, with an average of 3.7, and the percentage was 74.5%. The study recommended the necessity of expanding the channel’s broadcasting to reach European societies with all its components, in addition to working on opening a website on the Internet that broadcasts directly to the Western world.